2016
DOI: 10.4313/teem.2016.17.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on the Stability of Amorphous Indium Gallium Zinc Oxide Thin Film Transistors Using Amorphous Oxide Multilayer Source/Drain Electrodes

Abstract: In order to find suitable source and drain (S/D) electrodes for amorphous InGaZnO thin film transistors (a-IGZO TFTs), the specific contact resistance of interface between the channel layers and various S/D electrodes, such as Ti/Au, a-IZO and multilayer of a-IGZO/Ag/a-IGZO, was investigated using the transmission line model. The a-IGZO TFTs with a-IGZO/Ag/a-IGZO of S/D electrodes had good performance and low contact resistance due to the homojunction with channel layer. The stability was measured with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is found that some complex oxides have ferromagnetic, ferroelectric, and magnetoresistive effects, which allows complex oxides to be implemented into important applications in the field of microelectronics. For example, amorphous a-IGZO [103] and perovskite metal-oxides [104], have been exploited to facilitate the advancement of microelectronics under the bottleneck of Moore's law.…”
Section: Complex Metal Oxidesmentioning
confidence: 99%
“…It is found that some complex oxides have ferromagnetic, ferroelectric, and magnetoresistive effects, which allows complex oxides to be implemented into important applications in the field of microelectronics. For example, amorphous a-IGZO [103] and perovskite metal-oxides [104], have been exploited to facilitate the advancement of microelectronics under the bottleneck of Moore's law.…”
Section: Complex Metal Oxidesmentioning
confidence: 99%
“…Recently, attention has been focused on the zink based oxide (ZnO) semiconductors due to their superior characteristics that include a flexibility and transparency for application to electronic devices [1][2][3][4][5][6]. One promising candidate material for electronic device oxide semiconductors is a zink tin oxide (ZTO), made by mixing of ZnO : SnO 2 =1 : 1.…”
Section: Introductionmentioning
confidence: 99%